Meningkatkan Prestasi Belajar dan Bernalar Kritis Peserta Didik Fase F Pada PAKBP Menggunakan Model PBL Berbantuan Media Youtube - Dewi Anaria Sinurat; Sukestiyarno Sukestiyarno (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
The teacher is one of the main components that really determines the success of the teaching and learning process. Thus, teachers should create the right situations and conditions to enable the learning process in students by directing all resources and using appropriate teaching and learning strategies, which include approaches, methods and learning techniques. To overcome the low learning achievement of students, researchers conducted Classroom Action Research on class XII SMKN Catering Services students. 1 Simanindo by applying the Problem Based Learning learning model assisted by YouTube. This research aims to improve learning achievement and critical reasoning abilities in students. This research was conducted in two cycles. Each cycle consists of several stages, namely planning, implementing actions, observing and reflecting. Data collection techniques were carried out by means of tests and observations, with a descriptive approach. The results of the research increased from cycle 1 to cycle 2. In cycle 1 there were still students in the appropriate category in the learning achievement variable and the category began to develop in the critical reasoning variable, then entering cycle 2 there was an increase with no students in the appropriate category in learning achievement variable, and categories began to develop on the critical reasoning variable.